(untitled) (International Congress on Economics, Management and Business Studies, 2026)
In the development of human capital in our country, the development of education and healthcare systems plays an important role. The President of the Republic of Uzbekistan Shavkat Mirziyoyev, emphasizing the principle of economic and social development “From the great past to the great future”, emphasized the importance of the “Development Strategy of New Uzbekistan”, which includes such important areas as ensuring the rule of law, developing competition, and waging a sharp fight against corruption, for the country’s economy [1].